Psychology in South Asia - Ali, M. R.; Khaleque, A.; South Asian Association of Psychologists (Dhaka, Bangladesh) (Dhaka : Shakil Prokashoni in collaboration with South Asian Association of Psychologists, 1996)
Contributed articles.
Includes bibliographical references.
Keywords: Psychology -- South Asia -- History